"The Rippled Perceptions": The Effects of LGBT-Inclusive TV on Own Attitudes and Perceived Attitudes of Peers Toward Lesbians and Gays. (September 2019) - Yan, Harry Yaojun
This study explores the effects and influence of presumed influence of consuming recent lesbian, gay, bisexual, and transgender (LGBT)-inclusive TV on attitudes toward lesbians and gays (ATLG) and perceived attitudes toward lesbians and gays (PATLG) among peers. Adding to previous research, this study testifies to the modest yet positive effects of current entertainment narratives on viewers' ATLG. The results demonstrate dynamics of "the rippled perceptions ": people's own attitudes are the "origin of peer perceptions"; media consumption and interpersonal contact predict participants' own attitudes; the influence of presumed influence attenuates as the analysis moves from self, to close friends, and those of the same age.